Honor and shame in early China - Lewis, Mark Edward 1954- (Cambridge University Press, 2020)
In this major new study, Mark Edward Lewis traces how the changing language of honor and shame helped to articulate and justify transformations in Chinese society between the Warring States and the end of the Han dynasty. Through careful examination of a wide variety of texts, he demonstrates how honor-shame discourse justified the actions of diverse and potentially rival groups. Over centuries, the formally recognized political order came to be intertwined with groups articulating alternative models of honor. These groups both participated in the existing order and, through their own visions of what was truly honourable, paved the way for subsequent political structures. Filling a major lacuna in the study of early China, Lewis presents ways in which the early Chinese empires can be fruitfully considered in comparative context and develops a more systematic understanding of the fundamental role of honor/shame in shaping states and societies
Title from publisher's bibliographic system (viewed on 16 Nov 2020)
Keywords: Honor / History / Political aspects / China; Honor / History / Social aspects / China; Shame / History / Political aspects / China; Shame / History / Social aspects / China; China / History / 221 B.C.-960 A.D.